2022
DOI: 10.36689/uhk/hed/2022-01-005
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Work in Visegrad Group Countries

Abstract: The aim of this study is to examine the similarities and differences in the attitudes of people living in the Visegrad Group (V4) countries towards work. In the introduction to the study, we briefly discuss the establishment of the Visegrad Group and the peculiarities of the labor market in Slovakia, the Czech Republic, Hungary and Poland. Our research was based on secondary data. We examined some questions of the European Values Survey related to the world of work and then compared the results in the four cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The study found significant differences between the countries (between Hungary and Lithuania and Slovakia and Lithuania), but no significant differences were found between Hungary and Slovakia. All of the examined countries were part of the "Eastern Bloc" and are the members of European Union, but there are several overlaps in the history of Slovakia and Employee wellbeing in uncertain conditions Hungary, they are neighboring countries and are member of Visegrad Group among other cooperations (Kolosov and Wie ˛ckowski, 2018;Connelly, 2020;Ba sa and Ba sa, 2022). It is important to mention that Lithuania belongs to Baltic states, and as mentioned above, according to Jahn (2016), there is a clear difference between Baltic and Visegrad states in terms of the level of "neoliberalism".…”
Section: Third Step Of Micom Analysismentioning
confidence: 99%
“…The study found significant differences between the countries (between Hungary and Lithuania and Slovakia and Lithuania), but no significant differences were found between Hungary and Slovakia. All of the examined countries were part of the "Eastern Bloc" and are the members of European Union, but there are several overlaps in the history of Slovakia and Employee wellbeing in uncertain conditions Hungary, they are neighboring countries and are member of Visegrad Group among other cooperations (Kolosov and Wie ˛ckowski, 2018;Connelly, 2020;Ba sa and Ba sa, 2022). It is important to mention that Lithuania belongs to Baltic states, and as mentioned above, according to Jahn (2016), there is a clear difference between Baltic and Visegrad states in terms of the level of "neoliberalism".…”
Section: Third Step Of Micom Analysismentioning
confidence: 99%